The Stages of the Cultural Landscape Transformation of Seaside Resorts in Poland against the Background of the Evolving Nature of Tourism - Wojciech Bal; Magdalena Czalczynska-Podolska (Land, 2020)
The development of tourism determines the cultural landscape transformation, spatial development of coastal localities, scale of recreational architecture and other forms of development related to tourism services. The article presents research aiming to analyze tourism development in the context of its impact on the cultural landscape of Polish coastal localities, taking into account the specificity of post-communist countries and supra-regional tendencies. The main objective of this study was to analyze the development of tourism in the context of its impact on the cultural landscape seaside towns and to identify, on the basis of the changes, the nature of tourism and forms of recreation in particular stages of the shaping of elements in coastal locality spaces and recreational architecture. The research was based on historical-interpretation studies, field studies of selected coastal localities, including urban-planning inventories, landscape, and functional and spatial analyses. The research carried out resulted in the identification of the stages of the cultural landscape transformation of coastal localities and indication of characteristic features of architecture and landscape. The journey along the coastline is a temporal journey through the changing nature of buildings, allowing observation of the stage-by-stage nature of investment processes in response to the changing needs of tourists.